Christianity and the rhetoric of empire : the development of Christian discourse - Cameron, Averil (University of California Press, 1991)
Many reasons can be given for the rise of Christianity in late antiquity and its flourishing in the medieval world. In asking how Christianity succeeded in becoming the dominant ideology in the unpromising circumstances of the Roman Empire, Averil Cameron turns to the development of Christian discourse over the first to sixth centuries A.D., investigating the discourse's essential characteristics, its effects on existing forms of communication, and its eventual preeminence. Scholars of late antiquity and general readers interested in this crucial historical period will be intrigued by her exploration of these influential changes in modes of communication.
Keywords: Christian literature, Early -- Greek authors -- History and criticism.; Church history -- Primitive and early church, ca. 30-600.; Theology -- History -- Early church, ca. 30-600.; Christianity and other religions -- Greek.; Christianity and other religions -- Roman.; Greece -- Religion.; Rome -- Religion.; Littérature chrétienne primitive -- Auteurs grecs -- Histoire et critique.; Église -- Histoire -- ca 30-600 (Église primitive); Théologie -- Histoire -- ca 30-600 (Église primitive); Christianisme -- Relations -- Religion grecque.; Christianisme -- Relations -- Religion romaine.; Grèce -- Religion.; RELIGION -- Christian Church -- History.; RELIGION -- Christianity -- History.; Christian literature, Early -- Greek authors; Christianity; Church history -- Primitive and early church; Greeks -- Religion; Interfaith relations; Religion; Romans -- Religion; Theology -- Early church; Greece; Rome (Empire); Vroege kerk.; Klassieke oudheid.; Verkondiging.; Vroegchristelijke literatuur.; Cultuurverandering.; Retorica.; Romeinse rijk.; Littérature grecque -- Histoire et critique.; Christianisme et civilisation -- Histoire -- Église -- 30-600 (Église primitive); Théologie -- 30-600 (Église primitive); Religion grecque -- Relations -- Christianisme.; Rhétorique antique.; Littérature chrétienne primitive -- Histoire et critique.; Religion romaine -- Relations -- Christianisme.; 30-600; Christianity -- History; Criticism, interpretation, etc.; History